Identification of a dicer homologue gene (DCL2) in Nicotiana tabacum - Udriste, A. A.; Stan, V.; Radu, G. L.; Tabler, M.; Cucu, N. (Plant biology (Stuttgart, Germany), 2012)
Eukaryotes possess a mechanism that generates small interfering RNA (siRNA) and microRNA (miRNA) and use these to regulate gene expression at the transcriptional or post‐transcriptional level. These small RNAs (21–24nt) are processed from long double‐stranded RNA precursors by type III RNase enzymes, referred to as DICER or DICER‐LIKE proteins (DCLs). In Arabidopsis, there are four DCL genes and their role in small RNA biogenesis and silencing has been the subject of intense study. DCL2 is less well studied than the other DCL proteins although it is known to play a role in formation of natural antisense siRNA and may be involved in transitive silencing of transgene transcripts. This study provides basic genomic information on DCL2 in the Nicotiana tabacum (NtDCL2) gene family and its probable roles in plant growth and development.